Heart Rate Measurement System Based on Pulse Sensors with Pathophysiological Appearance - Yana Yohana; Yudith Yunia Kusmala; M. Reza Hidayat; Susanto Sambasri (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2019)
Measuring the number of pulses has been used in the medical world to determine stress, relaxation, physical fitness levels, and other medical conditions. Due to the importance of checking heart rate, it is necessary to have a portable and practical heart rate measuring device so that patients with heart disease will be easier to be monitored. The device is equipped with pulse sensor to measure the heart rate in real time and provide a beats per minute (BPM). The results of normal heart rate conditions, bradycardia, and tachycardia can be monitored using mobile device application based on the measured BPM. This can be seen as output voltage generated by the pulse sensor. This pulse sensor has an average percentage error of 1.77% and deviation of 2 that is relatively small compared to standardized devices. The device is connected to the mobile application by Bluetooth which the coverage is 11 up to 45 meters depends on the obstacles.